GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2019)
A dataset containing 267 species occurrences available in GBIF matching the query: { "and" : [ { "or" : [ "BasisOfRecord is Human Observation", "BasisOfRecord is Specimen" ] }, "HasCoordinate is true", "TaxonKey is Acanthina Fischer von Waldheim, 1807", "HasGeospatialIssue is false" ] }. The dataset includes 267 records from 18 constituent datasets: 17 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 14 records from Zoología Invertebrados - Malacología. 32 records from iNaturalist Research-grade Observations. 65 records from MAL. 4 records from Natural History Museum Rotterdam (NL) - Mollusca collection. 19 records from SOMBASE – Southern Ocean mollusc database: a tool for biogeographic analysis in diversity and evolution. 6 records from FBIP:ELM: Malacology Collections. 13 records from NMNH Extant Specimen Records. 1 records from CHAS Malacology Collection (Arctos). 3 records from Mollusca Collection - Museu Nacional/UFRJ. 1 records from MSB Host Collection (Arctos). 3 records from Invertebrates Collection of the Swedish Museum of Natural History. 8 records from Natural History Museum (London) Collection Specimens. 1 records from Invertebrate Zoology Division, Yale Peabody Museum. 25 records from UF Invertebrate Zoology. 30 records from Museum of Comparative Zoology, Harvard University. 3 records from Base de datos de la Sala de Colecciones Biológicas de la Universidad Católica del Norte (SCBUCN). 22 records from sarce_rockyshores. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences